The Effect Of Work Motivation And Work Environment On Employee Performance In Hospitals - Adam Kamajaya; Nina Nurani (Jurnal Ekonomi, 2024)
Hospitals need to utilize success factors such as employee performance measurement to achieve their vision and mission to compete in the Indonesian healthcare sector. Providing better human resources and services to local communities. Healthcare services must be of high quality, fair and affordable, and communication with patients needs to be improved. The purpose of this quantitative study is to determine the effect of work motivation and work environment on the performance of hospital employees. Talented employees are important for the growth of the company, and human resources are its most important assets. A good work ethic is absolutely necessary to improve employee performance and achieve positive growth in line with company goals.